Critical roles of lncRNA-mediated autophagy in urologic malignancies - Gan, Lifeng; Zheng, Liying; Zou, Junrong; Luo, Peiyue; Chen, Tao; Zou, Jun; Li, Wei; Chen, Qi; Cheng, Le; Zhang, Fangtao; Qian, Biao (Frontiers in Pharmacology, 2024)
Urologic oncology is a significant public health concern on a global scale. Recent research indicates that long chain non-coding RNAs (lncRNAs) and autophagy play crucial roles in various cancers, including urologic malignancies. This article provides a summary of the latest research findings, suggesting that lncRNA-mediated autophagy could either suppress or promote tumors in prostate, kidney, and bladder cancers. The intricate network involving different lncRNAs, target genes, and mediated signaling pathways plays a crucial role in urological malignancies by modulating the autophagic process. Dysregulated expression of lncRNAs can disrupt autophagy, leading to tumorigenesis, progression, and enhanced resistance to therapy. Consequently, targeting particular lncRNAs that control autophagy could serve as a dependable diagnostic tool and a promising prognostic biomarker in urologic oncology, while also holding potential as an effective therapeutic approach.